Commentary: Disappearing Into Another’s Words Through Poetry in Research and Education (LEARNing Landscapes, 2010)
Increasingly, researchers turn to literary and artistic forms such as drama, short story, and poetry to present data interpretations. Artistic representations of research highlight the contextual nature of knowledge, interconnections between research tale and teller, role of language in creating meaning, and serve to communicate with audiences beyond academic communities.This paper discusses use of poetic representations in qualitative research and then explores ways in which poetic representations could be used in public schools, their contributions to learning, and how they can be evaluated. Of most importance is that a sense of "play" be maintained so that language, form, and data become avenues for discovery and creativity.
Keywords: poetry; education; poetic representation; qulitative; play; language; form; data; discovery; creativity